BEBAN GANDA ANEMIA PADA REMAJA SMPN TEMPURAN KABUPATEN KARAWANG - Nur Melani Sari (Universitas Padjadjaran, 2018)
Anemia is commonly found in Indonesia especially in infants, children and adolescents. Adolescent suffering a double burden of anemia including iron deficiency anemia and carriers of thalassemia. Iron deficiency anemia can affect brain function, growth and development process , and weaken the immune system. Thalassemia is a chronic disease passed down from parents to their children. The symptoms of these two diseases are very difficult to distinguish, namely mild anemia and sometimes asymptomatic. The incidence of new cases needs to be controlled, one of them is by using screening tests and education to the community. This program was carried out in the form of increasing the knowledge of health workers, junior high school teachers and students regarding thalassemia and iron deficiency anemia regarding talasemia screening policy from the Health Ministry. The method used is survey, observation and socialization lecture. The results of this study showed an increase in knowledge of Tempuran Middle School students, teachers, and health workers after socialization of thalassemia. The voluntary level of students to join the anemia screening program was 81.89% in Combat 1 Junior High School, and 66.67% in Combat Middle School 2. The percentage of anemia in adolescent girls was 11.68%, while in boys it was 25.53%.